Perceived stress and coping strategies among emergency department nurses and emergency medical services staff during the fifth wave of COVID-19 in Iran: A cross-sectional correlational study - Z. Salami; N. Mozaffari; M.A. Mohammadi (Elsevier, 2023)
Background and Purpose: Emergency department (ED) nurses and emergency medical services (EMS) staff as the main parts of care on the front line of treatment during the outbreak of COVID-19 experienced great challenges in their work and life, which caused them a lot of stress. Since limited studies have investigated perceived stress and coping strategies among ED nurses and EMS staff in Iran, this study was conducted to investigate perceived stress and coping strategies among ED nurses and EMS staff during the outbreak of the fifth wave of COVID-19 in Ardabil, Iran. Materials and methods: This descriptive-analytical cross-sectional study was conducted on 327 ED nurses and EMS staff in 2021. The samples were selected by convenient sampling method, and data were collected by demographic and perceived stressors and coping strategies against the outbreak of COVID-19 questionnaires. Data were analyzed by SPSS (version 22) using descriptive (frequency, percentage, mean, and standard deviation) and analytical (Pearson correlation, t-test, and ANOVA) statistical tests and multiple linear regression analysis. Results: The most stressful factors were related to the transmission of the disease to the family and seeing the death of COVID-19 patients in front of their eyes. The most commonly used coping strategies were strict personal protective measures for all hospitalized patients and the use of clothes that the hospital prepared separately to reduce the transmission of the virus. The results of multiple linear regression showed employees' emotions (β = 0.429, p < 0.001), gender (β = 0.225, p < 0.001), coping strategies (β = 0.209, p < 0.001), stress-reducing factors (β = 0.124, p = 0.014), worry (β = −0.182, p < 0.001), and workplace (β = -0.149, p = 0.045) were effective predictors of perceived stress. Conclusion: Coping methods such as following strict personal protective measures, using special clothes, and seeing the recovery status of patients and colleagues were effective factors in reducing the perceived stress of health workers. Therefore, it is necessary to provide health workers with training on coping strategies and psychological support in the current crisis and possible epidemics in the future.